Trapezoidal Rule with MATLAB Program Example

Trapezoidal Rule Derivation

The derivation for obtaining formula for Trapezoidal rule is given by,

Trapezoidal Rule Derivation
Trapezoidal Rule Derivation

Example

Evaluate the integral x^4 within limits -3 to 3 using Trapezoidal rule.

Solution

Let y(x)=x^4

here a=-3 and b=3

therefore (b-a)=6

let ‘n’ be the number of intervals. assume n=6 in this case.

also h=(b-a)/n = 6/6 =1

x: -3  -2  -1  0  1  2  3

y: 81  16  1  0  1  16  81

According to trapezoidal rule:

answer= (h/2)*[(y1+y7)+2*(y2+y3+y4+y5+y6)]

answer=(1/2)*[(81+81)+2*(16+1+0+1+16)]

answer=115.

MATLAB Program for Trapezoidal Rule

%Created by myclassbook.org (Mayuresh)
 %Created on 24 May 2013
 %Question: Evaluate the integral X^4 within limits 3 to -3

clc;
 clear all;
 close all;

f=@(x)x^4; %Change here for different function
 a=-3;b=3; %Given limits
 n=b-a; %Number of intervals
 h=(b-a)/n;
 p=0;

for i=a:b
  p=p+1;
  x(p)=i;
  y(p)=i^4; %Change here for different function
 end

l=length(x);
 x
 y
 answer=(h/2)*((y(1)+y(l))+2*(sum(y)-y(1)-y(l)))

Image format

MATLAB code for Trapazoidal Rule
MATLAB code for Trapezoidal Rule

Example

Evaluate the integral 1/(1+x) within limits 0 to 6 using Trapezoidal rule.

Solution

Let y(x)=1/(1+x)

here a=0 and b=6

therefore (b-a)=6

let ‘n’ be the number of intervals. assume n=6 in this case.

also h=(b-a)/n = 6/6 =1

x: 0                  1                    2              3                  4               5               6

y: 1.0000   0.5000   0.3333   0.2500   0.2000   0.1667   0.1429

According to trapazoidal rule:

answer= (h/2)*[(y1+y7)+2*(y2+y3+y4+y5+y6)]

answer=2.0214.

MATLAB code for the Trapazoidal rule:

%Created by myclassbook.org (Mayuresh)
%Created on 24 May 2013
%Question: Evaluate the integral 1/(1+x) within limits 0 to 6

clc;
 clear all;
 close all;

f=@(x)1/(1+x); %Change here for different function
 a=0;b=6; %Given limits
 n=b-a; %Number of intervals
 h=(b-a)/n;
 p=0;

for i=a:b
  p=p+1;
  x(p)=i;
  y(p)=1/(1+i); %Change here for different function
 end

l=length(x);
 x
 y
 answer=(h/2)*((y(1)+y(l))+2*(sum(y)-y(1)-y(l)))

Image Format

MATLAB code for Trapazoidal Rule
MATLAB code for Trapezoidal Rule

If you like this article, please share it with your friends and like or facebook page for future updates. Subscribe to our newsletter to get notifications about our updates via email. If you have any queries, feel free to ask in the comments section below. Have a nice day!

Leave a Reply

Your email address will not be published. Required fields are marked *